A disease beyond reach: nurse perspectives on the past and present of tuberculosis control in South Africa. Issue 4 (2nd October 2018) - Dixon, Justin; Tameris, Michèle
Abstract : Although access to healthcare has improved since South Africa's democratic transition, neoliberal reforms have had detrimental effects on clinic-community and nurse-patient relationships, undermining efforts to control tuberculosis (TB). This article focuses upon the work of nurses in three public health clinics in the Western Cape, South Africa. We explore how they experienced, made sense of and grappled with the challenges of TB control, especially patients "defaulting" on medication. Paying particular attention to confrontations between nurses and patients, we build upon previous qualitative studies that have contested popular constructions of nurses as "rude" and "uncaring." We argue that patient blaming and scolding need to be understood in light of nurses having to tread a fine line between compassion and assertiveness, individual and public good against the backdrop of a dissonance between the theory and reality of TB control. Nurses' confrontational approaches are responses to the messy reality of TB control on the ground, solutions to which require attention to the socioeconomic and historical context of nursing and primary healthcare. In the absence of such attention, animosities between clinics and communities could continue being cyclically reproduced.